2023
DOI: 10.1111/cod.14281
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis elicited by insulin infusion sets: First case reported in Poland

Abstract: avoidance of some allergens, including corticosteroids, thiurams and 4-tert-butylphenol formaldehyde resin, is not possible. CONFLICT OF INTEREST STATEMENTLaurence Mainville has no conflict of interest to declare. Marie-Claude Houle received speaker's fees from Sanofi. Hélène Veillette received speaker's fees from AbbVie, Janssen, Novartis, Sanofi Genzyme, Bausch Health and Sun Pharma. She worked on advisory committees (Novartis, Sandoz, Pfizer, Sanofi Genzyme, Sun Pharma and UCB), and contributed to clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This also supports the finding that Dexcom G6 is not free from IBOA. The second patient was primarily sensitised from the use of IBOA‐containing infusion sets and 1 year later developed contact dermatitis from the Guardian 3 sensor with the culprit allergen remaining unknown 32 . Relevant to the third patient, Enberg et al reported a case of a 6‐year‐old who had ACD due to IBOA contained in the new Orbit microinfusion set linked with MyLife YpsoPump 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This also supports the finding that Dexcom G6 is not free from IBOA. The second patient was primarily sensitised from the use of IBOA‐containing infusion sets and 1 year later developed contact dermatitis from the Guardian 3 sensor with the culprit allergen remaining unknown 32 . Relevant to the third patient, Enberg et al reported a case of a 6‐year‐old who had ACD due to IBOA contained in the new Orbit microinfusion set linked with MyLife YpsoPump 33 .…”
Section: Discussionmentioning
confidence: 99%
“…5 case reports (n=6) were identified in this review that describe pediatric patients presenting with contact dermatitis from their diabetes devices. Two of these cases (n=3) describe patients without a history of atopic dermatitis (AD) who developed contact dermatitis reactions from multiple infusion sets and CGMs, with alternating brand use and site placement [19,20]. IBOA and other acrylates were identified [19] along with dipropylene glycol diacrylate (DPGDA) [20] as culprit allergens.…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…Two of these cases (n=3) describe patients without a history of atopic dermatitis (AD) who developed contact dermatitis reactions from multiple infusion sets and CGMs, with alternating brand use and site placement [19,20]. IBOA and other acrylates were identified [19] along with dipropylene glycol diacrylate (DPGDA) [20] as culprit allergens. In two of these patients, successful switching of devices resolved the lesions [20].…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%
“…In the years since, it has been confirmed that, apart from FreeStyle Libre, IBOA is a contact allergen detectable in: (i) the housing [ 35 ] (1.11 ± 0.12 μg/mL), adhesive [ 35 ] (0.26 μg/mL) and in the Enlite sensor itself [ 36 ] (10 μg/sensor) (Medtronic, Fridley, MN, USA); (ii) a tubeless insulin pump Omnipod [ 37 ] (5 μg/patch and 190 μg/sensor) (Insulet Corporation, Billerica, MA, USA); (iii) insulin infusions sets Paradigm MiniMed Quick-Set and Paradigm MiniMed Sure-T [ 38 ] (Medtronic, Fridley, MN, USA); (iv) insulin infusion set Accu-Chek Insight Flex (Roche Diabetes Care, Indianapolis, IN, USA) [ 38 ]; (v) in all following parts of the Medtrum A6 TouchCare (Medtrum Technologies, Shanghai, China): 1 μg in the sensor, 3 μg in the sensor adhesive patch, 30 μg in the insulin pump reservoir, 6 μg in the reservoir patch adhesive [ 39 ]. Initially, gas-chromatography-mass-spectrometry (GC-MS) analysis showed that the related Paradigm Minimed Silhouette infusion does not contain IBOA within detection limits [ 38 ], but a recent report of a 15-year-old boy from Poland suggests that the Silhouette set might still contain IBOA in untraceable amounts, but enough to elicit contact dermatitis [ 40 ]. Unfortunately, despite the ongoing saga of skin reactions towards diabetes medical devices, it has already been reported that the relatively new insulin pump system YpsoPump (Ypsomed, Burgdorf, Switzerland) also contains IBOA, and the first cases of ACD elicited by this device are known [ 41 ].…”
Section: Contact Dermatitis Triggered By Diabetes Medical Devicesmentioning
confidence: 99%